REDUÇÃO DE CUSTOS PROPORCIONADOS PELA UTILIZAÇÃO DA TECNOLOGIA BIM NA OBRA DE CONSTRUÇÃO DO COMPLEXO PRISIONAL DE ARAÇOIABA - Silva, Beatriz Carneiro Menezes; Gonçalves, Gabriela Torres; Palha, Rachel Perez (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Nowadays in constructions site, it's usual to have rework in some activities during the construction process. This can be attributed to the lack of specialized professionals to coordinate different typologies of projects. In this context, the present study aims to demonstrate and evaluate the use of clash detection tools using BIM Platforms to verify clash reports and coordinate the model as close to construction as possible. The concept of BIM (Building Information Modeling) is an innovative technology that has tools, platforms and environments to optimize and automatize the process of conflict detections among different projects. Based on this, a case study was conducted, in order to analyse the benefits brought with the use of the clash detection tool in the management of the construction of the Araçoiaba Prisional Complex. The methodology utilized consisted in the analysis of twenty Critical Analysis Report (CAR) developed by the firm responsible for the management of the construction of this project. The main goal of the case study was to verify the cost needed to solve the identified conflicts. The results of the study confirmed the advantages associated to verifying conflicts among different disciplines of projects by using BIM Technology.